Предмет: Алгебра,
автор: yuliagorda1
14x-(12x-(6-11x))+2x=x+13-8x
Ответы
Автор ответа:
0
14х-(12х-(6-11х))+2х=х+13-8х
14х-(12х+6+11х)+2х=х+13-8х
14х+12х-6-11х+2х=х+13-8х
14х+12х-11х+2х-х+8х=6+13
24х=19
х=19:24
х=0.79
14х-(12х+6+11х)+2х=х+13-8х
14х+12х-6-11х+2х=х+13-8х
14х+12х-11х+2х-х+8х=6+13
24х=19
х=19:24
х=0.79
Похожие вопросы
Предмет: Математика,
автор: nosenkosvetlana111
Предмет: Математика,
автор: deadinside66666
Предмет: Алгебра,
автор: Аноним
Предмет: Геометрия,
автор: JeremyFeed
Предмет: Математика,
автор: emotions2011